Empati dan Religiositas Sebagai Prediktor terhadap Pemaafan pada Mahasiswa Sekolah Tinggi Teologi Salatiga - Sri Lina Betty Lamsihar Simorangkir (Sekolah Tinggi Alkitab Jember, 2019)
This research was conducted to find out the possibility of empathy and religiosity as a predictor of forgiveness student Sekolah Tinggi Teologi Salatiga. Sample in observational it is student Sekolah Tinggi Teologi Salatiga that total of 71 people. Three types of scale: empathy scale, religiosity scale, and forgiveness scale. All gathered data were processed and analyzed using a parallel linear regression with statistic program windows version 17.00. By a regression analyzing was obtained to usufruct that empathy and religiosity as a predictor of forgiveness the students Sekolah Tinggi Teologi Salatiga. R²=0.292, F hitung= 13.999 significant level of 0.000